1996
DOI: 10.1128/iai.64.9.3870-3876.1996
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of plasmids with infectivity of Borrelia burgdorferi sensu stricto type strain B31

Abstract: The correlation of plasmid profiles with infectivity was investigated by using five clones of Borrelia burgdorferi sensu stricto strain B31 (ATCC 35210). Plasmid profiles were determined by pulsed-field and two-dimensional gel electrophoresis. The 50% infectious dose (ID 50) in hamsters was determined. The ID 50 of the clone that possessed a full complement of eight linear and three circular plasmids was 10 3 cells. The loss of the 27.5-and 40-kb linear plasmids did not decrease the infectivity of these cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(48 citation statements)
references
References 47 publications
(48 reference statements)
1
47
0
Order By: Relevance
“…This similarity was determined using a probe (kindly supplied by T. G. Schwan) from the 8.4 kb plasmid (data not shown). The precise relationship of our 9.0 kb plasmid to the 8.4 kb and other interesting and similarly sized B. burgdorferi plasmids (Champion et al, 1994;Dunn et al, 1994;Xu et al, 1996;Fraser et al, 1997), is yet to be determined.…”
Section: Discussionmentioning
confidence: 95%
“…This similarity was determined using a probe (kindly supplied by T. G. Schwan) from the 8.4 kb plasmid (data not shown). The precise relationship of our 9.0 kb plasmid to the 8.4 kb and other interesting and similarly sized B. burgdorferi plasmids (Champion et al, 1994;Dunn et al, 1994;Xu et al, 1996;Fraser et al, 1997), is yet to be determined.…”
Section: Discussionmentioning
confidence: 95%
“…The relative mobility of the two reactive bands detected from strain B31-CH3 (Fig. 1B, lane 1) suggested that they corresponded to the 28 kb and 54 kb linear plasmids lp28-1 and lp54 respectively (Barbour, 1991;Xu et al, 1996;Fraser et al, 1997). Only one plasmid, lp54, was detected in strain B31-CH100 (Fig.…”
Section: Rna Subtraction and Southern Analysis Using Subtractive Probesmentioning
confidence: 95%
“…After the isolation of clone 4a from a solid agar colony, passage through a BALB/c mouse for 4 weeks and re-isolation from the mouse (see Casjens et al, 1997a), it carried all of the plasmids whose sequences are known except for cp9, lp5, lp28-3 and lp28-4 (data not shown). The plasmids missing in clone 4a may well have been lost during the cloning/mouse passage procedure because Borrelia strains have often been found to lose one or more plasmids during laboratory propagation and cloning procedures (for example Barbour, 1988;Schwan et al, 1988;Persing et al, 1994;Norris et al, 1995;Xu et al, 1996).…”
Section: Twenty-two Replicons In One Bacterium?mentioning
confidence: 99%
“…The linear DNAs have covalently closed hairpin telomeres (Barbour and Garon, 1987;Hinnebusch et al, 1990;Hinnebusch and Barbour, 1991;Casjens et al, 1997b;Fraser et al, 1997). Most of the plasmids can be lost and are not required for propagation of the bacteria in culture, but loss of infectivity in mice often parallels plasmid loss (for example Barbour, 1988;Hyde and Johnson, 1988;Schwan et al, 1988;Norris et al, 1992;Sadziene et al, 1993b;Persing et al, 1994;Xu et al, 1996;Zhang et al, 1997; but see Casjens et al, 1997a). For brevity, we will refer to the Borrelia extrachromosomal DNA elements as`plasmids', even though some of them may be universally present and are probably essential in nature (see Marconi et al, 1996a;Casjens et al, 1997b;Tilly et al, 1997), carry genes that may be metabolically important (Margolis et al, 1994) or have never been lost in culture.…”
Section: Introductionmentioning
confidence: 99%